Serpantin . Serpantin . Serpentine . Серпантин - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interviews with artists; survey of new films and theatrical productions. Featured in the program: Zaitsev, Viacheslav (Fashion Designer); Kolobov, Evgenii (Conductor); Liubimov, IUrii (Director); Shterianov, Vladimir (Director); Kuranov, Aleksandr (Director); Viktiuk, Roman (Director); Vasil'ev, Vladimir (Ballet Dancer) Contributors: Zakharov, Mark (Anchor) Программа состоит из интервью с деятелями искусства; обзор новых фильмов и театральных постановок. В программе участвуют: Зайцев, Вячеслав (Модельер); Колобов, Евгений (Дирижер); Любимов, Юрий (Режиссер); Штерянов, Владимир (Режиссер); Куранов, Александр (Режиссер); Виктюк, Роман (Режиссер); Васильев, Владимир (Артист балета) Создатели: Захаров, Марк (Ведущий/Ведущая)